Long-term effects of alcohol consumption on cognitive function in seniors: a cohort study in China - Lizhen Han; Jinzhu Jia (BMC Geriatrics, 2021)
Abstract Background In the context of increasing global aging, the long-term effects of alcohol consumption on cognitive function in older adults were analyzed in order to provide rationalized health recommendations to the elderly population. Methods The study used the Chinese Longitudinal Healthy Longevity Survey (CLHLS) dataset, from which 5354 Chinese seniors aged 65–112 years were selected as the subjects, spanning the years 1998–2018. Data on alcohol, diet, activity, and cognition were collected by questionnaire and cognitive levels were judged by the Mini-Mental State Examination scale (also referenced to the Functional Assessment Staging Test). Data cleaning and preprocessing was implemented by R software. The dynamic Cox model was applied for model construction and data analysis. Results The results of the dynamic Cox model suggested that seniors who drank alcohol were at higher risk of cognitive decline compared to those who never drank (HR = 1.291, 95%CI: 1.175–1.419). The risk was similarly exacerbated by perennial drinking habits (i.e., longer drinking years, HR = 1.008, 95%CI: 1.004–1.013). Compared to non-alcoholic beverages, liquor (≥ 38°), liquor (< 38°), wine and rice wine all showed negative effects. Whereas, the risk of cognitive decline was relatively lower in seniors who consumed liquors (< 38°) and rice wine compared to the high-level liquor (HR: 0.672 (0.508, 0.887) and 0.732 (0.559, 0.957), respectively). Conclusions Alcohol consumption has a negative and long-term effects on cognitive function in seniors. For the elderly, we suggested that alcohol intake should be avoided as much as possible.